TECTONICS OF THE HOT SPOTS ON VENUS, COMPARISON WITH THE EARTH - Nikishin A.M. (My University, 1990)
Domelike volcanic uplifts are widespread on Venus. The author has compiled a map of such uplifts and coronae for the comparatively well studied northern part of Venus, as well as the less well known southern part of that planet. It is based on a 1.5,000,000 geologic map. All researchers concur that the various types of domal volcanic uplifts identified on Venus formed above hot spots of the mantle. The tectonics associated with hot spots on Earth have been widely discussed in the literature. A comparison of structures assumed to be formed above the hot spots in the earth mantle clearly demonstrates the essential differences in the distribution of structures generated over the hot spots of the terrestrial and Venusian mantles.